40 Years of Discipline and Punish: A Rumor Under Harsh Times - Barbosa, Antônio Rafael (2017)
In the first part of this article, I present some features of Discipline and Punish that allow to recognize this book as a classic of the human sciences, as well as its importance in shaping the field of studies on violence and crime in Brazil (composing an introduction marked by its brevity and essayistic tone). In the second part of the text, I develop a more accurate reflection on the conceptual pair illegalism/delinquency presented by Foucault and I try to indicate some uses of such concepts for research related to prisons, crime and government control policies.